METODE SNOWBALL THROWING DENGAN PENGAJARAN BERBASIS INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DI SMP NEGERI 4 SURABAYA - Nurhaya, Dwi; Intan Puspita Sari; Hamzah Hamdani; Mohammad Rokib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In general, the implementation of Indonesian language learning in junior high schools currently often experiences obstacles. The facts that occur show that Indonesian is still a subject that is difficult to understand when seen from the students' learning outcomes. This is known based on researchers' observations at SMP Negeri 4 Surabaya that student learning outcomes in Indonesian language subjects are still relatively low. This is caused by the inappropriate method of teaching Indonesian that is presented so that it does not attract students' interest in learning Indonesian. This research is classroom action research. In the collection that will be carried out, test, observation and documentation techniques will be used. The results of the entire cycle show that there has been an increase in various aspects, namely the average score, classical completeness, and the number of students completing. Before being given the Snowball Throwing method in Inquiry-based teaching, the total number of students completing was 11 out of a total of 32 students with a completeness percentage of 35.5% and an average score of 69.76. In cycle 1, the total number of students completing was 19 out of a total of 32 students with a completion percentage of 65.2% and an average score of 65%. In cycle 2, the number of complete students obtained was 28 out of a total of 32 students with a complete percentage of 80.34% and an average score of 83.58.